Modelling activity novelty and adolescent females' subjective well-being during a winter holiday. Issue 4 (1st October 2016) - Drewery, David; Jiang, Kai; Hilbrecht, Margo; Mitas, Ondrej; Jakubowitz, Anna
ABSTRACT: Leisure research on adolescent females' holiday experiences, and how these experiences may contribute to their happiness is scarce. Recent work in the area of positive psychology has suggested that novelty within an experience may enhance positive emotions and life satisfaction which together comprise subjective well-being (SWB), a common conceptualization of happiness. The purpose of this paper was to test the direct influence of activity novelty and the mediating influence of emotion balance (the balance between positive and negative emotions) on life satisfaction for a group of adolescent females on a winter holiday. As part of a larger study, participants ( n = 74) were German girls aged 12–17 years who completed a diary-based questionnaire for 21 consecutive days (before, during, and after their holiday). A conditional process analysis indicated that activity novelty may have a positive or negative influence on emotion balance depending on pre-vacation activity novelty patterns. Furthermore, while novelty does not have a direct influence on life satisfaction, it has a positive indirect influence through emotion balance. This study provides evidence that holiday experiences can contribute to young women's SWB and highlights the important role of emotions during such experiences. In addition, results support the use of a positive psychology framework to understand adolescent vacationers' experiences.